2020
DOI: 10.3934/jdg.2020026
|View full text |Cite
|
Sign up to set email alerts
|

Pricing equilibrium of transportation systems with behavioral commuters

Abstract: We study Wardrop equilibrium in a transportation system with profit-maximizing firms and heterogeneous commuters. Standard commuters minimize the sum of monetary costs and equilibrium travel time in their route choice, while "oblivious" commuters choose the route with minimal idle time. Three possible scenarios can arise in equilibrium: A pooling scenario where all commuters make the same transport choice; A separating scenario where different types of commuters make different transport choices; A partial pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Third, due to data limitation, we focus mainly on the impact of the COVID-19 pandemic on ride-sharing supply, and our analysis on the impact of COVID-19 on ride-sharing demand is limited to the average trip distance. It would be interesting to collect passenger data and directly explore the impact of the pandemic on the demand side, especially when passengers act as behavioral commuters (Lien et al, 2020). Finally, since our data are from one single ride-sharing company, we have abstracted away from competition between ride-sharing companies and drivers' multihoming behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, due to data limitation, we focus mainly on the impact of the COVID-19 pandemic on ride-sharing supply, and our analysis on the impact of COVID-19 on ride-sharing demand is limited to the average trip distance. It would be interesting to collect passenger data and directly explore the impact of the pandemic on the demand side, especially when passengers act as behavioral commuters (Lien et al, 2020). Finally, since our data are from one single ride-sharing company, we have abstracted away from competition between ride-sharing companies and drivers' multihoming behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Second, by analyzing driver behavior in response to COVID-19, we add to the literature on labor supply in the taxi industry and, more recently, in the ride-sharing industry. In the taxi industry, it has been demonstrated that drivers exhibit reference-dependent preferences (Camerer et al, 1997;Crawford and Meng, 2011), respond positively to both unanticipated and anticipated increases in earning opportunities (Farber, 2015), strategically respond to surge pricing (Cachon et al, 2017;Castillo, 2018;Miao et al, 2021), overtreat passengers under a usage-based pricing scheme (Miao and Chu, 2020), and are strategic in location choices (Buchholz, 2017). In the ride-sharing industry, prior research has demonstrated flexibility in drivers' schedules and labor supply (Hall and Krueger, 2016;Chen et al, 2019), and the importance of external incentives (Allon et al, 2018;Brodeur and Nield, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%